Insolvency Law in the Czech Republic and in the USA Comparison of Reorganization Proceedings of Kordárna and General Motors Corporation - Beránek, Jaromír (2011)
Insolvency law is a progressive and dynamic legal discipline closely interrelated with economics and business. A quality legal framework of insolvency is indispensable for modern market economies: it helps to identify companies or individuals in financial distress and to restructure their debts, or liquidate their assets in an efficient and transparent way. The main purpose of the insolvency law is to provide creditors and debtors with a ground for negotiations and to help them reach qualified decisions based on the available information. In the Czech Republic, the insolvency law had long been criticized for its insufficient protection of creditors and for the loopholes that made extensive property frauds possible without having the wrongdoers punished. The current Czech Insolvency Act which took effect in 2008 was broadly inspired by the U.S. Bankruptcy Code Chapter 11 and eliminated most of the weaknesses of the earlier law. This thesis shows that valuable inspiration can be found not only in texts of statutes but also in the real life. On the example of reorganizations of Kordárna and GM described here, main principles of insolvency law are being discussed.